FACTORS INFLUENCING YOUTHS’ ENTREPRENEURIAL INTENTION: A CASE STUDY IN THE MEKONG DELTA - Truong , Thi Kim; Nguyen , Tri Khiem (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Youth entrepreneurship is particularly important in the Mekong Delta, where young people are expected to contribute to local employment, innovation, and the region’s green and digital transformation. However, existing studies on entrepreneurial intention (EI) in Vietnam have mainly focused on major urban areas or single-university samples, while evidence from the Mekong Delta remains limited. Therefore, this study aims to identify the factors influencing EI among youth in the Mekong Delta region of Vietnam. A mixed-methods research design was adopted, integrating both qualitative and quantitative approaches. Survey data were collected from 188 young individuals who are either currently engaged in or preparing for entrepreneurial activities, using a 5-point Likert scale for measurement. The analysis was conducted using PLS-SEM in SmartPLS, following two stages: assessment of the measurement model and the structural model. The results confirm the reliability of the measurement scales. The model explains 96.1% of the variance in EI (R² = 0.961). All hypotheses were supported at the p < 0.001 level with positive path coefficients: entrepreneurial motivation (EM) (β = 0.298), AT (β = 0.267), entrepreneurship support policies (SP) (β = 0.261), creativity and innovation (CI) (β = 0.245), and perceived behavioral control (PB) (β = 0.234). These findings underscore the prominent role of motivation, along with the importance of attitude, creative capacity, perceived control, and policy effectiveness in shaping EI among youth in the Mekong Delta. Managerial implications suggest prioritizing interventions that nurture motivation, enhance self-efficacy, foster innovation, and improve policy implementation to effectively convert intention into entrepreneurial action.